Pengaruh Profitabilitas, Likuiditas, Ukuran Perusahaan Terhadap Nilai Perusahaan Dengan Struktur Modal Sebagai Variabel Intervening - Lukmanul Hakim (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2022)
This study aims to examine the effect of profitability, liquidity, firm size on firm value with capital structure as an intervening variable (Empirical Study on Property and Real Estate Companies Listed on the Indonesia Stock Exchange 2016-2020 Period). The population in this study were 45 companies. The sampling technique used is purposive sampling and the number of samples is 21 companies with 5 years of observation, so that the sample data after observation becomes 105. The model used in this study is panel data regression using the Eviews 8 . application. The results of the study: Firm size and capital structure have a positive and significant effect on firm value, profitability and liquidity have a negative and significant effect on firm value. Profitability, liquidity, firm size and capital structure together have a positive and insignificant effect on firm value